Holmium Laser Enucleation of the Prostate and Iatrogenic Arteriovenous Fistula Treated by Superselective Arterial Embolization - Anastasios D. Asimakopoulos; Lorenzo Dutto; Paolo Preziosi; Enrico Spera; Francesco Micali; Andrea De Carolis; Beniamino Iorio (Case Reports in Urology)
Iatrogenic pelvic pseudoaneurysm with concomitant arteriovenous fistula has been described as a rare and challenging complication, which may occur during transurethral resection of the prostate. We provide the first report of this complication after holmium laser enucleation of the prostate for the treatment of benign prostatic hyperplasia. The attempt to control the bleeding by conversion to open surgery and placement of haemostatic stitches into the prostatic fossa failed. Angiography with superselective arterial embolization proved to be a modern, quick, safe, and efficient treatment of this uncommon complication.